2021
DOI: 10.1001/jamapsychiatry.2021.2588
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use, Methamphetamine Use Disorder, and Associated Overdose Deaths Among US Adults

Abstract: IMPORTANCE Mortality associated with methamphetamine use has increased markedly in the US. Understanding patterns of methamphetamine use may help inform related prevention and treatment. OBJECTIVE To assess the national trends in and correlates of past-year methamphetamine use, methamphetamine use disorder (MUD), injection, frequent use, and associated overdose mortality from 2015 to 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 42 publications
4
127
0
2
Order By: Relevance
“…No recent opioid-specific interventions were identified, which is surprising given the drastic increase in opioid use-related deaths over the past decade particularly in the United States [20]. Furthermore, the literature on psychostimulants interventions is particularly scarce, even though research has indicated that frequent use of psychostimulants has increased drastically in recent years in various high-income countries [21]. Therefore, it would be desirable to increase the focus of digital interventions targeting opioid and psychostimulant use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…No recent opioid-specific interventions were identified, which is surprising given the drastic increase in opioid use-related deaths over the past decade particularly in the United States [20]. Furthermore, the literature on psychostimulants interventions is particularly scarce, even though research has indicated that frequent use of psychostimulants has increased drastically in recent years in various high-income countries [21]. Therefore, it would be desirable to increase the focus of digital interventions targeting opioid and psychostimulant use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine use in the US increased 43% from 2015 to 2019 [106]. Methamphetamine use alters the immune system in a variety of ways, including altered immune cell subset number, increased pro-inflammatory cytokine production, increased CD4+ and CD8+ T cell proliferation, enhanced CD4+ T cell activation and/or exhaustion, and altered immune-related signaling pathways, as reviewed elsewhere [107][108][109][110].…”
Section: Stimulants and Hivmentioning
confidence: 99%
“…Methamphetamine use is deemed to associate with not only physical harms including HIV transmission ( Shoptaw and Reback, 2007 ), cardiovascular disease ( Darke et al, 2017 ; Kevil et al, 2019 ), cerebrovascular disease ( Lappin et al, 2017 ) but also psychiatric harms including psychosis, depression, anxiety and suicide In 2019, it is estimated that as much as 0.5% of global population aged between 15 and 64 had used the amphetamine-type stimulants [ United Nations Office on Drugs and Crime (UNODC), 2021 ]. From 2010 to 2018, the prevalence of methamphetamine use within the general population in the United States over the past year has increased by 195% ( Paulus and Stewart, 2020 ), and the number of overdose deaths attributed to psychostimulant use has tripled over the previous 5 years in 2019 ( Han et al, 2021 ). Despite the negative effects of such methamphetamine use on society, current treatments are inadequate, and no pharmacological treatments have been approved for any stimulant use disorders.…”
Section: Introductionmentioning
confidence: 99%